Synthesis of π-extended B ← N coordinated phenanthroimidazole dimers and their linear and nonlinear optical properties. Issue 23 (2nd June 2020) - Vanga, Mukundam; Sa, Shreenibasa; Kumari, Anupa; Murali, Anna Chandrasekar; Nayak, Prakash; Das, Ritwick; Venkatasubbaiah, Krishnan
Abstract : B ← N coordinated phenanthroimidazole dimers exhibit excellent fluorescence quantum yields in solution and conjugation length dependant two-photon-absorption properties. Abstract : Intramolecular B ← N coordinated fluorophores have shown potential applications in optoelectronics and as sensors due to their unique photophysical properties. In this work, we report the synthesis and characterization of π-conjugated boron doped phenanthroimidazole dimers. All the π-conjugated B ← N coordinated phenanthroimidazole dimers exhibited high quantum yields in solution (up to 99%) and moderate quantum yields in the solid state (up to 51%). We investigated the nonlinear optical properties of phenanthroimidazole dimers and found that the measurement of two-photon-absorption cross-section is correlated with the conjugation length.